Prenatal Yoga and Childbirth Education: A Response to Tracy Posner's Birth Story - Israel, Ann L. (Lamaze International Inc., 2010)
In this letter to the editor, the author responds to a birth story published in a previous issue of The Journal of Perinatal Education and discusses the relationship between practicing prenatal yoga and childbirth education.